A digital manuscript case study: How publishing theory can advance the practice of manuscript digitization. Issue 1 (1st June 2013) - Tether, Leah
Using Gérard Genette''s seminal work on 'paratexts' (defined by Genette (1997) as extratextual items which fundamentally influence a reader's reception of a text, such as, for example, blurbs, jacket designs, prefaces, etc.), this article undertakes a practical enquiry into the ways in which digital media have been used to render the paratexts of medieval manuscripts. Reference to an existing project, Christine de Pizan: the Making of the Queen's Manuscript, is made so as to form a case study on this area, one that acts representatively, due to its use of software features, methods and tools that have been applied in a number of digital/medieval projects. This case study will constitute a lens for exploring how successfully manuscriptural paratexts are represented by completed digitization projects by applying Genette's theory of paratextual spaces. The article will then consider some of the latest developments in digital tools for medievalists under the same light so as to see how differently such projects can now be approached. Ultimately, the article will explore how the broader application of publishing theory could move manuscript digitization projects forward because, just as book publishing actually constitutes an exercise in content packaging – which is traditionally the realm of publishing professionals – the process of creating digital manuscripts, and digital editions of medieval texts, represents a closely related undertaking.